A semi-analytical solution for energy harvesting via the elastic motion of the circular floater of aquaculture cages attached with piezoelectric. (August 2022) - Gharechae, Ataollah; Abazari, Abuzar; Ketabdari, Mohammad Javad
Abstract: This work's unique research objective is to assess the possibility of energy harvesting by attaching the piezoelectric patches on the high-density polyethylene floater of aquaculture fish cages. Using Euler-Bernoulli's curved beam theory, the vertical elastic motion of the floater in regular linear sea waves was modeled semi-analytically based on slender body theory and matched asymptotic expansions. Regular linear waves refer to the single frequency waves with small amplitudes compared to the wavelength, for which the linear airy wave theory can approximate the wave characteristics. When the floater elastic motions are determined, the resultant strain is implemented to the governing equation of piezoelectric patches to calculate the generated power. The effect of some variables such as wavenumber, floater bending stiffness, relative floater dimension, and the number of patches in the circumference of the floater on the generated power was investigated. The results indicate that by installing the patches in the proper place, the floater can produce the required electrical power supplying some low-powered electric sensors for monitoring sea environmental conditions or other applications. Also, as a suggestion, installing piezoelectric patches throughout the perimeter of a semi-submerged circular elastic floater is a way of energy harvesting from sea waves.